Erectile Dysfunction and COVID-19: a Case Report - Gembong Satria Mahardhika; Nastiti Maharani; Theodore Dharma Tedjamartono; Efriadi Ismail (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Coronavirus Diesease-2019 (COVID-19) infection is suspected to affect the sexual behavior and function. The vascular damage related to COVID-19 can affect the impairment of bed blood vessel of penile and finally make the erectile dysfunction (ED). This problem is one of the most common sexual problem in man, with the prevalantion between 13 until 28% at the 40-80 years old, and the incidence increases with higher age. At this time, no data about the effect of COVID-19 to sexual behavior. There was one case of COVID-19 with erectile dysfunction who was treated at Kemayoran Athletes Village COVID-19 hospital. Erectile dysfunction is influenced by several factors; including psychogenic, neurogenic, and infectious. The diagnosis of erectile dysfunction is determined based on the results of history taking and physical examination, using the standard questionnaire (IIEF-5/International index of erectile function-5). A further review is needed to exclude a particular cause, the management can be determined based on the etiology.